Expert consensus on regenerative endodontic procedures - Xi Wei; Maobin Yang; Lin Yue; Dingming Huang; Xuedong Zhou; Xiaoyan Wang; Qi Zhang; Lihong Qiu; Zhengwei Huang; Hanguo Wang; Liuyan Meng; Hong Li; et al. (Nature Publishing Group, 2022)
Abstract Regenerative endodontic procedures (REPs) is a biologic-based treatment modality for immature permanent teeth diagnosed with pulp necrosis. The ultimate objective of REPs is to regenerate the pulp-dentin complex, extend the tooth longevity and restore the normal function. Scientific evidence has demonstrated the efficacy of REPs in promotion of root development through case reports, case series, cohort studies, and randomized controlled studies. However, variations in clinical protocols for REPs exist due to the empirical nature of the original protocols and rapid advancements in the research field of regenerative endodontics. The heterogeneity in protocols may cause confusion among dental practitioners, thus guidelines and considerations of REPs should be explicated. This expert consensus mainly discusses the biological foundation, the available clinical protocols and current status of REPs in treating immature teeth with pulp necrosis, as well as the main complications of this treatment, aiming at refining the clinical management of REPs in accordance with the progress of basic researches and clinical studies, suggesting REPs may become a more consistently evidence-based option in dental treatment.